A diversidade de macrófitas altera a comunidade de invertebrados e a dieta de peixes. - Yofukuji, Kátia Yasuko (2020)
The diversity of aquatic macrophytes provides different local conditions, containing more microhabitat than homogeneous systems, thus supporting diverse biotic communities. Considering that the diversity of these plants can affect the invertebrate community and, consequently, the associated fish diet, this study assessed the influence of macrophyte diversity on the abundance, richness, and diversity of invertebrates, and the diet of Moenkhausia forestii. Fish, invertebrates, and macrophytes were sampled in macrophyte stands with different diversities, distributed along with a 14 km extension of the coastal region of Rio Baía (Upper Paraná River floodplain). The stands were separated into low, medium and high diversity, and they all had biomass that did not differ significantly. The invertebrates associated with the macrophytes and those consumed by M. forestii were identified and counted. Differences in abundance, richness, and diversity of invertebrates between levels of macrophyte diversity (low, medium and high) were tested using an ANOVA. Differences in the composition of the M. forestii diet were tested using a PERMANOVA, and feeding selectivity was calculated using the Ivlev index. Richness, diversity, and abundance of invertebrates were greater in high diversity macrophyte stands, however, for abundance, there was no significant difference between the levels of macrophyte diversity. The diet of M. forestii differed significantly between stands, and aquatic plants were the most used resource in low diversity. Invertebrates were dominant in high diversity, while aquatic plants and invertebrates were important in medium diversity of macrophytes. These results indicate that invertebrate communities were influenced by the diversity of macrophytes since richer and more diverse communities were also associated with more diverse stands of these plants. Changes observed in the diet of M. forestii were also associated with the diversity of macrophytes. In a scenario where involving changes in the attributes of these plants, and these stands become dominated by one or a few species of macrophytes, it is expected that this will reflect on other trophic levels, even at a local scale.